Global Constitutionalism A Socio-legal Perspective - Atilgan, Aydin (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, Veröffentlichungen des Max-Planck-Instituts für ausländisches öffentliches Recht und Völkerrecht,, 2018)
This book provides insights into the viability of the idea of global constitution. Global constitutionalism has emerged as an alternative paradigm for international law. However, in view of the complex and varied structure of contemporary constitutionalism, in reality it is extremely difficult to use constitutional law to provide a new paradigm for international law. The book argues that the cultural paradigm can offer functional tools for the global constitutionalism discourse. In other words, global constitutionalism could be handled in the context of a global "constitutional culture" instead of a global constitution. This would provide a more realistic basis for discussing global constitutionalization of a society as diverse as the international community, where a globalized polity and a globalized legal system have not yet been achieved.